TANGGUNG JAWAB PENDIDIKAN DALAM PERSPEKTIF PSIKOLOGI AGAMA - Shabri Shaleh Anwar (Psympathic : Jurnal Ilmiah Psikologi, 2014)
In the perspective of the religion psychology, education is responsible for the students’ development. Education in terminology is a conscious effort to change students’ attitudes and behavior towards maturity, with one of indicator is the ability to take responsibility and trust. Responsibility is man's consciousness on his/her behavior, whether intentionally or not, and has a sense of meaning embodiment obligations. Responsible ability built through the education process includes responsibility vertically (to The God), horizontal responsibility (to the something outside himself or someone else), and personal responsibility